Socio-Economic Life of Fishermen's Community in Padang City - Syahrizal; Meiyenti, Sri; Mitra, Robi; Ihsan, Shahibul; Ramdesta, Andry (Universitas Medan Area, 2024)
This article aims to describe the socio-economic life of the fishing community in Purus Village, Padang City. The problem in the article concerns the socio-economic conditions of fishing communities in Padang City. This research was conducted on fishing communities in Purus Village, Padang City using ethnographic qualitative methods through observation, structured interviews, in-depth interviews, and document analysis. The results of the research can be concluded: First, the reason for choosing a job as a fisherman is because this job is a job passed down from ancestors; they feel destined to be fishermen, do not have the capital to open another business, have a low level of education, and have no other skills. Second, the relationship between fishermen and their family members is not very close, because they are busy with their respective activities until the afternoon. Third, education in fishing families is generally only limited to middle and high school, because the costs are considered expensive and children lack motivation to study and continue their education to tertiary level. Fourth, there are still many fishing communities that do not have their own homes and live in simple rented houses. Fifth, income from fishing in the sea is uncertain, like a 'tiger's fortune', sometimes you get quite a lot of fish, and sometimes you don't catch any fish. The lack of socio-economic welfare of the fishing community in Purus, Padang City is influenced by unstable economic income.